Reeder and Felson’s Gamuts in Neuro-Radiology Comprehensive Lists of Roentgen and MRI Differential Diagnosis - Reeder, Maurice M.; Bradley, William G. (Springer New York, 1993)
All the gamuts pertaining to the nervous system have been excerpted into this book from Reeder and Felson's Gamuts in Radiology, the world's best known, most trusted, and most comprehensive guide to radiologic differential diagnosis. Clinicians are given easy access to complete lists of possible causes that guide the interpretation of findings or patterns on MR, CT, angiography, and plain film studies. The user-friendly listings are concise and well organized. They are arranged by relative frequency to help radiologists, neuroradiologists, and residents arrive at an immediate diagnosis. Other features include a slim 5"x8" trim size for handy portability and an easy-to-read single-column format. This ideal pocket guide is a must have for everyday use in clinical practice and is also an excellent teaching tool and study guide for board exams
Keywords: Neuroradiology; Neurology; Neurosurgery; Radiology, Medical; Krankheit; Radiologische Diagnostik; Differentialdiagnose; Kernspintomografie; Nervensystem